Efforts to Address Nutritional Problems in Toddlers: Literature Review - Anggie Diniayuningrum; Adinda Putri Belladina; Isna Hudaya (Jurnal Keperawatan Profesional, 2026)
The toddler period is an important stage in a child's life because during this time there is rapid growth and development, physically, psychologically, and motorically. Nutritional problems in toddlers remain a concern a public health challenge in Indonesia. The prevalence of stunting in toddlers shows a decreasing trend from 12.1% in 2013 to 10.2% in 2018 and 7.4% in 2019, but it increased again to 7.7% in 2022. This study aims to examine various efforts to address nutritional problems in toddlers based on previous research findings. The method used was a literature review through searching for articles in the Google Scholar and PubMed databases with inclusion criteria of articles published from 2021 to 2025 and discussing nutritional interventions in toddlers. A total of 12 articles that met the inclusion criteria were analyzed. The results of the review showed that efforts to address nutritional problems in toddlers include nutrition education for mothers, provision of supplementary foods and supplementation, as well as integrated nutritional interventions. It can be concluded that integrated and sustainable nutritional interventions are effective in improving the nutritional status of toddlers.